1997
DOI: 10.1038/sj.ijo.0800529
|View full text |Cite
|
Sign up to set email alerts
|

Leptin is a physiologically important regulator of food intake

Abstract: OBJECTIVE: These studies were designed to test the hypothesis that endogenous leptin, acting within the brain plays a physiologically important role in the control of food intake in lean rats. DESIGN: Antibodies directed against mouse leptin were raised in rabbits. The puri®ed IgG fractions prepared from pre-immune and immune sera were injected into the right lateral ventricle of lean Sprague-Dawley rats and obese Zucker fatty faafa rats. Changes in food intake were measured over the following 20 h period. RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 34 publications
2
25
1
1
Order By: Relevance
“…This conclusion is in accord with previous ®ndings, showing that polyclonal antibodies directed against leptin increase food intake in free-feeding lean rats. 22 The results of the present studies clearly show R128Q leptin to be an antagonist of leptin in vitro, but to behave as an agonist in vivo. The reason for this paradox is unclear at the present time.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…This conclusion is in accord with previous ®ndings, showing that polyclonal antibodies directed against leptin increase food intake in free-feeding lean rats. 22 The results of the present studies clearly show R128Q leptin to be an antagonist of leptin in vitro, but to behave as an agonist in vivo. The reason for this paradox is unclear at the present time.…”
Section: Discussionsupporting
confidence: 48%
“…Previous studies in free-feeding lean rats have shown that the injection of rabbit anti-mouse leptin antibodies into the brain markedly increases food intake during the light phase. 22 No increase in food intake was observed in obese Zucker faafa rats expressing a defective functional leptin receptor. These observations imply that the presence of leptin in the brain contributes tonically to the inhibition of food intake observed at this time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations